Efficient electrochemical water oxidation in neutral and near-neutral systems with a nanoscale silver-oxide catalyst. Issue 32 (29th July 2016) - Joya, Khurram S.; Ahmad, Zahoor; Joya, Yasir F.; Garcia-Esparza, Angel T.; de Groot, Huub J. M.
Abstract : A nanoscale silver-oxide electrocatalyst, anodically generated in a simple HCO3 − /CO2 system, is a highly stable and robust material for sustained water oxidation. Abstract : In electrocatalytic water splitting systems pursuing for renewable energy using sunlight, developing robust, stable and easily accessible materials operating under mild chemical conditions is pivotal. We present here a unique nanoparticulate type silver-oxide (AgOx-NP ) based robust and highly stable electrocatalyst for efficient water oxidation. TheAgOx-NP is generated in situ in a HCO3 − /CO2 system under benign conditions. Micrographs show that they exhibit a nanoscale box type squared nano-bipyramidal configuration. The oxygen generation is initiated at low overpotential, and a sustained O2 evolution current density of >1.1 mA cm −2 is achieved during prolonged-period water electrolysis. TheAgOx-NP electrocatalyst performs exceptionally well in metal-ion free neutral or near-neutral carbonate, phosphate and borate buffers relative to recently reported Co-oxide and Ni-oxide based heterogeneous electrocatalysts, which are unstable in metal-ion free electrolytes and tend to deactivate with time and lose catalytic performance during long-term experimental tests.